2020
DOI: 10.1016/j.stem.2019.12.008
|View full text |Cite|
|
Sign up to set email alerts
|

Pathogenic Potential of Hic1-Expressing Cardiac Stromal Progenitors

Abstract: The cardiac stroma contains multipotent mesenchymal progenitors. However, lineage relationships within cardiac stromal cells are still poorly understood. Here, we identify heartresident PDGFRa + Sca-1 + cells as cardiac Fibro/Adipogenic Progenitors (cFAPs) and show that they respond to ischemic damage by generating fibrogenic cells. Pharmacological blockade of this differentiation step with an anti-fibrotic tyrosine kinase inhibitor decreases post-myocardial infarction (MI) remodeling and leads to improvements… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 55 publications
(27 reference statements)
3
75
0
Order By: Relevance
“…As such, although inactive in vivo, the FAP CD90+ have an increased propensity to enter the cell cycle, which is associated with a larger cell size. This finding suggests that FAP CD90+ could be a subset of progenitor cells within FAPs that is poised for entry into cell cycle and further fibrogenic activation, as proposed for cardiac FAPs 53 . To examine this further, we decided to perform the limiting dilution and single-cell clonal assay.…”
Section: Thy1 Marks a Specific Subpopulation Of Skeletal Muscle Fapsmentioning
confidence: 69%
“…As such, although inactive in vivo, the FAP CD90+ have an increased propensity to enter the cell cycle, which is associated with a larger cell size. This finding suggests that FAP CD90+ could be a subset of progenitor cells within FAPs that is poised for entry into cell cycle and further fibrogenic activation, as proposed for cardiac FAPs 53 . To examine this further, we decided to perform the limiting dilution and single-cell clonal assay.…”
Section: Thy1 Marks a Specific Subpopulation Of Skeletal Muscle Fapsmentioning
confidence: 69%
“…Two very recent studies have identified a subpopulation of perivascular MSCs in the heart and muscle, which are characterized by the expression of PDGFRα, stem cell antigen-1 (Sca-1, Ly6A) and the tumor repressor hypermethylated in cancer 1 (Hic1) (Scott et al, 2019;Soliman et al, 2020). Both studies have shown that Hic1 + MSCs play important roles in the homeostasis and repair of heart and skeletal muscle, differentiate into different cell types including fibroblasts and are kept in a resting state by Hic1 (Kim and Braun, 2020).…”
Section: A Disrupted Msc Niche Leads To Loss Of Regenerative Potentiamentioning
confidence: 99%
“…Both studies have shown that Hic1 + MSCs play important roles in the homeostasis and repair of heart and skeletal muscle, differentiate into different cell types including fibroblasts and are kept in a resting state by Hic1 (Kim and Braun, 2020). The transcription repressor Hic1 is required for maintaining quiescence, since deletion of Hic1 leads to activation and expansion of MSCs, and subsequently leads to pathological fibrosis of heart (Soliman et al, 2020) and skeleton muscle (Scott et al, 2019), respectively. The exact molecular targets of Hic1 remain elusive.…”
Section: A Disrupted Msc Niche Leads To Loss Of Regenerative Potentiamentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate a role of FAPs in ACM, researchers verified the expression of desmosome proteins, found only in adipogenic but not in fibrogenic subpopulations [35]. Experiments on mice revealed that the inhibition of FAPs fibrogenic differentiation could be a therapeutic strategy after myocardial infarction, but further studies on human models are necessary [36].…”
Section: Fibro/adipocyte Progenitorsmentioning
confidence: 99%